PROVISION OF NECESSARY TEACHING AND LEARNING NEEDS FOR IMPROVING ACADEMIC PERFORMANCE OF STUDENTS WITH VISUAL IMPAIRMENT IN TANZANIA INCLUSIVE SECONDARY SCHOOLS - Karuhawe, Celestine D. G. (International Journal of Research -GRANTHAALAYAH, 2021)
This paper focuses on provision of necessary teaching and learning needs for improving academic performance of students with visual impairment study- ing in inclusive private as well as public secondary schools in Tanzania. It was guided by the following three specific objectives: to analyse reasons for provid- ing necessary teaching and learning needs of students with visual impairment in Tanzania inclusive secondary schools; to assess types of teaching and learn- ing needs that are necessary in provision of education for VI students in Tanza- nia inclusive secondary schools; to highlight significance of providing necessary teaching and learning needs to students with visual impairment in Tanzania inclusive secondary schools. The Open System’s Model was adapted in conducting this study. The model provides pieces of advice for provision of education under the following stages: input, process, and output to enable students learn efficiently as well as per- form better in studies and examinations. In its pursuit, the study applied qualitative research approach and a case study design. Qualitative research approach and the case study allowed the researcher to avoid biases by sup- porting researched information with clear facts as advised in rules of credibil- ity, transferability, dependability, and confirmability. Twenty-four participants selected under purposive sampling procedure were involved in the study. Semi- structured interviews and focus group discussions were the employed data col- lection methods. The researcher insists that necessary teaching and learning needs should always be provided in Tanzania inclusive secondary schools for students with visual impairment. Their significance is to facilitate students’ les- son understanding and better performance in examinations. Good examination results will assure parents and the government on extent to which education provided in the country meets intended national goals. It should be maintained by making provision of such needs a continuous process.